Migrant's pursuit of happiness. The impact of adaptation, social comparison and relative deprivation: evidence from a 'natural' experiment - Melzer, Silvia Maja; Muffels, Ruud J.A. (Berlin, 2012)
"The German reunification, which several economists have called a 'natural' experiment, provides the unique possibility to inquire the impact of migration on subjective well-being (SWB). The main goal of the research is to assessing the impact of adaptation, social comparison and relative deprivation on the change in SWB associated with moving from Eastern to Western Germany after the German reunification in 1989. We suspect that the gains or losses in subjective well-being after migration are affected by the way migrants adapt to their new economic conditions, by with whom migrants compare themselves (that is, their reference group), their former peers in the East or their new peers in the West, and how well they integrate into the new society, that means whether they are relatively deprived with respect to earnings or not. We estimate fixed- and random-effects Generalized Least Square panel regression models. Our results indicate a positive and lasting effect of migration on SWB, although it is strongly suppressed by dissatisfaction resulting from the comparison of migrants' income with the incomes of their former peers in East Germany and the relatively higher earnings of their new peers in West Germany. Moreover, our analyses provide an explanation for the increase of SWB associated with an increase in income found in East Germany after the reunification; a deviation from the Easterlins' paradox."